Libraries as redistributive technology: From capacity to culture in Queensland's public library network. (August 2018) - Wyatt, Danielle; Mcquire, Scott; Butt, Danny
Australia is currently rolling out one of the most expensive and ambitious infrastructure projects in the nation's history. The National Broadband Network is promoted as a catalyst for far-reaching changes in Australia's economy, governmental service provision, society and culture. However, it is evident that desired dividends, such as greater social engagement, enhanced cultural awareness and increased civic and political participation, do not flow automatically from mere technical connection to the network. This article argues that public institutions play a vital role in redistributing technological capacity to enable emerging forms of social and cultural participation. In particular, we examine public libraries as significant but often overlooked sites in the evolving dynamic between digital technology, new cultural practices and social relations. Drawing on interviews and fieldwork across the public library network of the state of Queensland, we attend to the strategies and approaches libraries are adopting in response to a digital culture.